Forget psychotic symptoms for a moment: what about memory, learning and problem-solving? Cognitive impairment in schizophrenia and the need for new treatments. - Newcomer JW (Journal of the California Alliance for the Mentally Ill, 1996)
A closer look at information processing, learning and memory in persons with schizophrenia.